India at the crossroads : sustaining growth and reducing poverty - Callen, Tim; Reynolds, Patricia, 1961-; Towe, Christopher M., 1957- (International Monetary Fund, 2001)
The authors examine the numerous structural and policy changes Indian authorities have adopted since the 1991 balance of payments crisis; how these changes helped India weather the Asian financial crisis of 1997-98; the risks to fiscal sustainability and their implications for growth; the challenges facing monetary policy in the face of financial market liberalization; and the benefits of structural reform and fiscal policy for growth, poverty, and the reduction of regional disparities.